Jawaban Soal PAT

JAWABAN SOAL PAT

1.
a = i - 8j + 5k
    b = 3i + 2j + 2k
    c = -2i - 4j + 3k 

a + 2b - 3c
(1)         (3)      (-2)
(-8) +2  (8) -3  (-4)
(5)         (2)       (3)

(1)     (6)      (-6)
(-8) + (16) -  (-12)
(5)      (4)      (9)
= 13i + 20j


2. (7)     (1)
    (-4) × (8) = 0
    (p)     (-5)

 7 + (-32) - 5p = 0
-25 = 5p
p = -5

a - b - c
(7)    (1)    (1)
(-4) - (8) - (-2) = ( 5, -10, -3 )
(-5)   (-5)  (-3)


3. PQ = Q - P
(-4)  (9)
(1) - (11) = ( -13, -10 )


4. AB = k × BC
B - A = k × C - B
(7)       (1)            (15)    (7)
(-14) -  (-5) = K × (-26) - (-14)
(6)       (-9)            (20)    (6)

(6)            (8)
(-9) = K × (-12)
(15)          (14)

6 = K × 8
K = 6/8
K = 3 : 4


5. AB = B - A
(2)     (-3)   (5)
(-1) -  (5) = (-6)
(8)     (2)    (6) ~ U

BC =C - A
(3)    (-3)   (6)
(-4) - (5) = (-9)
(6)    (2)     (4) ~ V

U × V 
(5)     (6)
(-6) × (-9) = 30 + 54 + 24
(6)     (4)  = 108


6. a = PQ = Q - P
(-4)     (-8)     (-3)
(20) -  (-4)  = (24)
(10)    (-15)   (25)

QR = R - Q
(12)   (-11)   (23)
(22) - (20) = (2)
(-20)  (10)    (-30)

PR = R - P
(12)   (-8)    (20)
(22) - (-4) = (26)
(-20)  (-15)   (-5)

b = QR - PR
(23)   (20)   (3)
(2)  -  (26) = (-24)
(-30)  (-5)     (-25)

a × b
(-3)     (3)
(24) × (-24) = - 9 - 576 - 625
(25)    (-25) = - 1.210


7. a = PR = R - P
(3)     (-1)      (4)
(15) - (10) = (5)
(0)     (0)       (0)

b = PQ = Q - P
(5)   (-1)     (6)
(3) - (10) = (-7)
(0)   (0)       (0)

c = QR = R - Q
(3)     (5)    (-2)
(15) - (3) = (12)
(0)      (0)    (0)

c = ma + nb
(-2,12) = m(4,5) + n(6,-7)
-2,12 = (4m,5m) + (6n,-7n)

4m + 6n = -2 | ×5 | 20m + 30n = -10
5m - 7n = 12 | ×4 | 20m - 28n = 48  -
> 58n = -58
> n = -1

4m + 6n = -2
4m + 6(-1) = -2
4m - 6 = -2
4m = 4
m = 1


8. u × v 
(5)     (1)
(-6) × (p) = 5 × 6p + 8 = 0
(-2)    (-4)= 6p = -13
                = p = 2,1 ~ 2


9. c = a - b
(5i + 6j - 2k) - (3i - 4j - 13k)
2i + 10j + 11k

=√ 2² + 10² + 11²
√4 + 100 + 121
√225 = 15


10. a = PQ = Q - P
(6)    (3)     (3)
(0) -  (-6) = (6)
(12)  (9)     (3)

b = QR = R - Q
(3)    (6)    (-3)
(-9) - (0) = (-9)
(18)  (12)  (6)

|a| = √3² + 6² + 3³
√9 + 36 + 9
√54 = 3√6

|b| = √-3³ + (-9²) + 6²
√9 + 81 + 36
√126 = 3√14

Cos0 = a × b / 3√6 × 3√14
(3)    (-3)
(6) × (-9) / 9√22 = -9 - 54 + 18 / 9√22
(3)    (6)          = 45 / 9√22 = -5/√22 × √22/√22
                        = -5√22 / 22

Cos0 = -1,06
          = 122°


11. Cos0 = v × w / |v| × |w|
|v| = √4 + 16 + 4
√24 = 2√6

|w| = √1 + 1 + 4
√6

(2)     (1)
(-4) × (1) / 2√6 × √6 = 2 - 4 - 4 / 12
(-4)    (2)                    = -6 / 12 = - 1/2 = 120°


12. g = A - B
(3)    (5)     (-2)
(-9) - (-8) = (-1)
(-5)   (-8)    (3)

h = C - D
(11)    (10)   (1)
(-12) - (-9) = (-3)
(-2)      (-4)    (2)

|g| = √4 + 1 + 9 = √14
|h| = √1 + 9 + 4 = √14

(-2)    (1)
(-1) × (-3) / √14 × √14 = - 2 + 3 + 6 / 14
(3)     (2)                        = 7/14 = 1/2 = 60°


13. ab = √7 × 2√3 = 2√21
ab = a² + 2ab + b²
a+b² ,= 7 + 2( 2√21) + 12
a+b = √19 + 4√21
19 + 84
103


14. AB = (7) ~ B - A
                (4)
                (-9)

AB = B - A
(7)          (8)
(4) = B - (-11)
(-9)         (3)
B = (7)    (8)        (15)
       (4) + (-11) = (-7)
       (-9)   (3)        (-6)


15. a = v - u
(9)   (5)    (4)
(3) - (3) = (0)
(-3)  (-3)   (0)
|a| = √16 = 4

b = w - v
(13) (9)    (4)
(7) - (3) = (4)
(-3)  (-3)   (0)
|b| = √32 = 4√2

Cos0 = a × b / |a| × |b|
(4)    (4)
(0) × (4) / 4 × 4√2 = 16 + 0 + 0 / 16√2
(0)    (0)                  = 16/16√2 × 16√2 / 16√2
                                = 1/√2 × √2/√2
                                = 32√2/32 = √5 × 1/2√2
                                = 45° /315°
Tan 45° = 1
Tan 315° = -1


16. |v| = √25 + 9 + p²
|v|² = 34 + p

|u| = 1/2 × v
1/2 × (34 + p)
17 + 1/2p

u × v / |v| = 
(-1)   (-5)
(4) × (3) / 17 + 1/2p = 5 + 12 + 6p / 17 + 1/2p
(6)    (p)                      = 17 + 6p / 17 + 1/2p
                        17+6p = 17 + 1/2p
                                 0 = 3p
                                 P = o/3 = 3


17. u × v = 1/2 v
17 + 6p / 34 + p = 1/2 (34 + p)
17 + 6p / 34 + p = 17 + 1/2p
17 + 6p = 17 + 1/2p × 34 + p
17 + 6p = 578 + 17p + 17p + 1/2p
17 + 6p = 578 + 17p
- 578 = 11p
P = -51

Komentar

Postingan populer dari blog ini

PERSAMAAN EKSPONENSIAL